PERAN SOSIAL GURU AGAMA DALAM MEMBINA KERUKUNAN UMAT BERAGAMA DI MASYARAKAT YANG MAJEMUK - Asep Kurniawan (Edueksos : Jurnal Pendidikan Sosial & Ekonomi, 2013)
Abstrak Social conditionsare determined by education. There is a strong relationship between education and society, and vice versa.It makes the position of the teachers, as part of the education and the public,are very important, especially in building religious harmony in a pluralistic society.In fact, it is not uncommonthat the use of religion in conflict and violence based on errors in interpreting and understanding the teachings of religion, and then obviously it is related to education.Means that education (in this case is religious education) has failed to fulfill its role and functions to generate religious man correctly and mutual respect.Therefore, pluralisticlife in the community - no doubt - should be a harmonization of life with the involvement of the social competence of Islamic teachers.He must be able to act as religious leaders as well as community leaders who educate, resolve conflicts, mediate, and being a role model, so that inter-religious harmony can be built up and maintained. Key Words: guru agama, masyarakat, plural, kerukunan, pembinaan